Internationally recruited neonatal nurses' experiences in the National Health Service in London. Issue 4 (26th March 2014) - Alexis, Obrey; Shillingford, Adeline
<x xml:space="preserve">Abstract</x> The aim of this study was to explore internationally recruited neonatal nurses' (IRNNs) perceptions of their experiences of working in the National Health Service (NHS) in London. This was an exploratory study. A purposive sample of 13 nurses (all females) from two teaching hospitals in London participated in this study. Semi‐structured face‐to‐face interviews were used to capture IRNNs views of working in the NHS in London. Five themes emerged, namely: motivation to migrate, lack of preparation for neonatal nurses, environmental conditions impacting on care delivery, neonatal nurses deskilling, and role restrictions as well as professional development. The findings of this study provide first‐hand insights from the subjective perspectives of IRNN experiences. IRNNs experienced some challenges to their working lives; however, good preparation is important when recruiting them to work in the NHS.